Genetic Determinants of White Matter Hyperintensities on Brain Scans: A Systematic Assessment of 19 Candidate Gene Polymorphisms in 46 Studies in 19 000 Subjects - Paternoster, Lavinia; Chen, Wanting; Sudlow, Cathie L.M. (Stroke (1970), 2009)
Background and Purpose— White matter hyperintensities (WMH) are highly heritable and associated with small artery ischemic stroke, so they may be a useful trait for studying the genetics of small vessel disease. Many studies have attempted to find associations between polymorphisms in various candidate genes and WMH. We aimed to evaluate the evidence for these associations by performing a systematic review and series of meta-analyses. Methods— We used a comprehensive search strategy to identify studies of the association between any genetic polymorphism and WMH. For all polymorphisms in genes studied in >2000 subjects we performed meta-analyses, calculating pooled odds ratios or standardized mean differences. Results— We identified 46 studies of polymorphisms in 19 genes in ≈19 000 subjects. Most genes were involved in lipid metabolism, control of vascular tone, or blood pressure regulation. Polymorphisms in the apolipoprotein E, angiotensin-converting enzyme, methylenetetrahydrofolate reductase, and angiotensinogen genes had been studied in >2000 subjects and were evaluated by meta-analysis. There was no evidence for an association between apolipoprotein E (ε4+/−), methylenetetrahydrofolate reductase (677 cytosine/thymine polymorphism [C/T]), or angiotensinogen (Met235Thr) and WMH. For the angiotensin-converting enzyme insertion/deletion polymorphism (I/D) there appeared to be a significant association (OR, 1.95; 95% CI, 1.09–3.48), but this may be partly attributable to the small study (mainly publication) and other biases. Conclusion— No genetic polymorphism has yet shown convincing evidence for an association with WMH. Much larger studies will be needed to detect and confirm genetic associations with this promising trait in the era of genome-wide association studies.